AKTIVITAS DIURESIS Leucaena leucocephala.L PADA MENCIT JANTAN (Mus musculus) - Muhammad Ricky Ramadhian; Khairil Pahmi; Muhammad Taupik (Journal Syifa Sciences and Clinical Research, 2021)
Diuretics are compounds or drugs that can increase urine volume. This study focused on exploring the activity and concentration of ethanol extract of lamtoro leaves (Leucaenaleucocephala L.) as a diuretic in male house mice (Musmusculus) using experimental research. The method used was to observe the physical activity of urine produced for 120 minutes. Lamtoro leaves extraction was done by maceration using solvent ethanol, then phytochemical screening tests. The screening results stated positively contained alkaloids, flavonoids, terpenoids, and tannins. The animals used were 25 house mice, divided into 5 groups. Group 1 was given Na-CMC 1% w/v suspension, group 2 with furosemide suspension 0.0041% w/v, group 3 with 25% w/v lamtoro leaf ethanol extract, group 4, ethanol extract 50% w/l lamtoro leaf , and group 5 was ethanol extract 75% w/v of lamtoro leaves. Urine volume of the house mice was measured at 15, 30, 45, 60, 75, 90, 105, and 120 minutes.